2015 IEEE Aerospace Conference 2015
DOI: 10.1109/aero.2015.7119227
|View full text |Cite
|
Sign up to set email alerts
|

A framework for orbital performance evaluation in Distributed Space Missions for earth observation

Abstract: Abstract-Distributed Space Missions (DSMs) are gaining momentum in their application to earth science missions owing to their unique ability to increase observation sampling in angular, spatial, spectral and temporal dimensions simultaneously. DSM architectures have a large number of design variables and since they are expected to increase mission flexibility, scalability, evolvability and robustness, their design is a complex problem with many variables and objectives affecting performance. There are few open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…temporal, angular, sp ectral and radiometric [5]. DSMs encompass a diverse family of spacecraft configurations.…”
Section: Multi-angular Remote Sensingmentioning
confidence: 99%
See 4 more Smart Citations
“…temporal, angular, sp ectral and radiometric [5]. DSMs encompass a diverse family of spacecraft configurations.…”
Section: Multi-angular Remote Sensingmentioning
confidence: 99%
“…The mission will not only need precise relative fo rmation flight but also strict attitude control, orbit maintenance, onboard processing for the mUlti-spectral data, inter-satellite calibration and a good communication channel to downlink the collected data. Parallel studies have demonstrated availability of fe asible orbits and their performance trade offs [5], payload development [22] to support such a mission, science models to quantify the performance of such DSMs [2], [12], [13] as well as open-source flight software to continually update satellite capability for staged, scalable deployment [25]. This paper fo cuses on quantitative methods to evaluate such a mission's development and operational fe asibility within achievable COTS (Commercial Off-The Shelf) technologies identified in Reference [26], satellite vendor websites and mission-tested components.…”
Section: Proposing a New Me Asurement Solutionmentioning
confidence: 99%
See 3 more Smart Citations